Experiences and strategies adopted for the implementation of pharmaceutical services in hospital geriatric units: A scoping review protocol - Alan Maicon de Oliveira; Fabiana Rossi Varallo; Leonardo Régis Leira Pereira (Elsevier, 2023)
Background: Pharmaceutical care is considered an important pillar for promoting the rational and safe use of medicines. Consequently, it constitutes actions of practices capable of reducing morbidity and mortality induced by pharmacotherapy. On the other hand, pharmaceutical services may face several barriers related to the implementation of these practices. These difficulties are associated with management, availability of an appropriate physical environment, integration with the multidisciplinary team, and acceptance of pharmaceutical interventions by health professionals. Objectives: This study aims to map and summarize the scientific evidence on the experiences and strategies used to implement pharmaceutical services in hospital geriatric units. Methods: The scoping review will be based on three electronic databases (PubMed, EMBASE, and Web of Science). Studies that met the inclusion criteria and are published by December 2022 will be selected. The screening, eligibility, extraction, and assessment of studies will be carried out by two independent researchers. Experimental and observational studies will be eligible for inclusion. Discussion: The experiences of incorporating pharmaceutical care into geriatric hospital units need to be better disseminated. Our review could support the performance of pharmaceutical care in other geriatric wards and has the potential to be a reference for multidisciplinary training. In addition, the study is related to the global challenge of the World Alliance for Patient Safety as it is a survey that will demonstrate strategies for safety in the use of medicines.